2013
DOI: 10.5624/isd.2013.43.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Effective dose from direct and indirect digital panoramic units

Abstract: PurposeThis study aimed to provide comparative measurements of the effective dose from direct and indirect digital panoramic units according to phantoms and exposure parameters.Materials and MethodsDose measurements were carried out using a head phantom representing an average man (175 cm tall, 73.5 kg male) and a limbless whole body phantom representing an average woman (155 cm tall, 50 kg female). Lithium fluoride thermoluminescent dosimeter (TLD) chips were used for the dosimeter. Two direct and 2 indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
11
0
4
Order By: Relevance
“…25 Whether a difference in radiation dose is reflected in the image quality and the diagnostic outcome was not investigated, nor was this issue within the scope of the present study. A previous study by Molander et al 4 concluded that Scanora (dental) provided the best subjective image quality.…”
Section: Discussionmentioning
confidence: 94%
“…25 Whether a difference in radiation dose is reflected in the image quality and the diagnostic outcome was not investigated, nor was this issue within the scope of the present study. A previous study by Molander et al 4 concluded that Scanora (dental) provided the best subjective image quality.…”
Section: Discussionmentioning
confidence: 94%
“…These values are slightly higher than measurements found in other studies using the Rando adult phantoms and TLDs [6,[17][18][19][20][21]. In a study by Davis et al, [22] the effective dose measured using a short collimator was 7.7 microsieverts.…”
Section: Discussionmentioning
confidence: 60%
“…However, several limitations of these radiographs were noted in the literature (1)(2)(3)(4)(5)(6). For instance, the image quality of these films is not as sharp as intraoral radiographs.…”
Section: Introductionmentioning
confidence: 99%